Microscopy investigation of platinum ternary alloy catalysts on n-doped reduced graphene oxide supporter for direct ethanol fuel cell (Defc) - Naruephon Mahamai (2020)
© 2020 Trans Tech Publications Ltd, Switzerland. Platinum (Pt) is widely used as anode catalyst for direct ethanol fuel cell (DEFC) but toxic CO gas was produced in the system. Pt bimetallic catalysts can increase the reaction rate, current density and reduce CO gas production. However, some bimetallic catalysts are still expensive and give the low reaction rate. Trimetallic catalysts on carbon supporter were represented instead due to their better catalytic activities, long life time of operation and higher current density. In this study, we synthesized trimetallic alloy on N-doped reduced graphene oxide (NrGO) catalysts using as DEFC anode. The percentage of metals composition in the synthesized catalysts was varied. NrGO was prepared by Modified Hummers Method, then reduced by annealing under Nitrogen gas atmosphere and N-added by annealing with melamine. The preparation method for trimetallic alloy catalysts on NrGO was NaBH4 reduction. The X-ray diffraction (XRD) patterns displayed their alloy phase of PtMRu (M = Au, Sn) which compose of Pt main structure and NrGO supporter. Scanning Electron Microscopy (SEM) images showed the dispersion of alloy metal particles on NrGO surface. The composition of catalysts could be confirmed by Energy dispersive spectroscopy (EDS) data and the phase of alloy particles were verified by electron diffraction (SAD) patterns. Transmission Electron Microscopy (TEM) images showed the particle size of PtAuRu and PtSnRu in various specific percentage on NrGO. The approximate particle size for 10Pt2Au8Ru = 4.88±1.02 nm, 10Pt5Au5Ru = 58.45±42.16 nm, 10Pt8Au2Ru = 11.05±2.29 nm, 10Pt2Sn8Ru = 3.31±1.44 nm, 10Pt5Sn5Ru = 3.50±0.73 nm and 10Pt8Sn2Ru = 4.09±0.97 nm. Catalytic activity of these materials related to their particle size.